Research on the Current Situation and Countermeasures of State owned Assets Management in Administrative Institutions - Yang, Yanqing; Gan, Yu (International Journal of Global Economics and Management, 2024)
As a socialist country with a dominant public ownership system, the core status of public ownership is significantly reflected in the State's control and guidance over the key sectors of the national economy. As the representative of all citizens in the country, the State is the sole owner of state-owned assets. Therefore, effective management of state-owned assets is an objective necessity to promote the development of the national economy and a necessary requirement to maintain the basic economic system of the country. The core task of the audit agency is to ensure the transparency, compliance, and maximum efficiency of fiscal and financial spending, thereby implementing comprehensive and effective supervision. In this process, auditing the state-owned assets of administrative and public institutions is an indispensable part. This paper analyzes the weak links and causes of the management of state-owned assets in municipal administrative and public institutions in Yibin City based on the special audit process of municipal state-owned assets. Using resource value theory and property rights theory, the study finds that the management of state-owned assets in municipal administrative and public institutions is characterized by weak foundation management, unregulated lease management, inadequate use management, and low efficiency in project property rights processing. In order to enhance the management efficiency of state-owned assets by administrative and public institutions, each unit should: 1. Strengthen the professionalism and capabilities of managers; 2. Establish a sound system of state-owned asset management; 3. Optimize the allocation of state-owned asset management; 4. Clarify the scope of state-owned asset management; and 5. Improve the information management of state-owned assets.